Quality assessment of heatstroke videos on TikTok - Qiu, Jun; Zhou, You-Lian (Frontiers in Public Health, 2024)
The prevalence of heatstroke is increasing as a result of global warming. Heatstroke is a serious but preventable condition, underscoring the urgent need to disseminate relevant health education to the general public.The advent of new technologies has facilitated more convenient and rapid access to health information. In recent years, short videos have emerged as a primary medium for disseminating health education. The short-video application TikTok has gained considerable popularity among the general public. However, the quality of heatstrokerelated health education content on TikTok deserves closer scrutiny.The purpose of this study was to evaluate the information about heatstroke videos available on TikTok.The present study analyzed the top 100 heatstroke-related short videos on TikTok, focusing on the characteristics of the videos, their quality, and the content they conveyed. The quality of these videos was assessed using the DISCERN instrument. In addition, the completeness of the videos was assessed by examining six key aspects: disease definition, clinical manifestations, risk factors, assessment, management, and outcomes.The study included a total of 90 videos. The results showed that news organization and health professionals were the primary contributors of videos, with those from news organizations receiving the most attention, while those from healthcare professionals received comparatively less engagement. The quality of messages was found to be moderately low overall, with the highest quality videos posted by nonprofit organizations, followed by those posted by health professionals. The majority of videos provided a description of the disease definition, clinical presentation, risk factors, assessment, management, and outcomes of heatstroke.The overall quality of information provided in short videos on TikTok about heatstroke is inadequate and needs improvement. In addition, such content should be subject to government review to ensure its accuracy and reliability.